Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation. (30th October 2018) - Davy, Barbara; Quilley, Stephen
Abstract : Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.